Formation of extremely fine water droplets in sheared, concentrated bitumen solutions via surfactant-mediated tip streaming. (15th September 2016) - Sonthalia, Rohit; Ng, Samson; Ramachandran, Arun
Highlights: Microfluidic setup to study drop breakup dynamics in concentrated bitumen solutions. Extremely fine water droplets produced via tip streaming under industrial conditions. Naphthenic acids, not asphaltenes, are responsible for tip streaming. Abstract: After extraction via surface mining, bitumen froth is purified by reducing its particle and water content in the naphthenic froth treatment section. The ineffectiveness of this treatment in reducing water content below 2 wt% is, however, known only too well, and arises primarily due to the exceedingly small sizes of the emulsified water droplets. Using a flow-focusing microfluidic device, we demonstrate a possible mechanism for the formation of fine water droplets – surfactant-mediated tip streaming. Via this mechanism, a drop, when sheared in a flow, can produce droplets that can be more than two orders of magnitude smaller than the parent drop. The capillary number, which represents the strength of flow-induced drop stretching forces relative to shape-restoring interfacial tension forces, was found to range between 0.35 and 0.9 to observe tip streaming. It was discovered that naphthenic acids, and not asphaltenes, are the primary interfacially-active species responsible for tip streaming. Higher bitumen dilutions, which reduce viscosity contrast, and higher basic pH, which amplifies interfacial concentrations and decreases interfacial tension gradients, were found to suppress tip streaming. It was also demonstrated that even a mere second of exposure of water droplets to flow conditions conducive to tip streaming is capable of producing a volume fraction of micron/sub-micron water droplets comparable to the residual water fraction in bitumen after froth treatment.